The Real World Journey of Implementing Fall Prevention Best Practices in Three Acute Care Hospitals: A Case Study. (25th June 2012) - Ireland, Sandra; Kirkpatrick, Helen; Boblin, Sheryl; Robertson, Kim
ABSTRACT Background Globally, falls are the second leading cause of unintentional injury. In Canada, falls that occur in hospitals have been ranked second as an area of patient safety concern. Many Canadian hospitals seeking to achieve patient safety, accreditation and resource containment goals are implementing evidence‐based practices in fall prevention. However, best practices are reported to be only variably effective in reducing hospital fall rates, indicating a potential gap in our understanding of the implementation process. This study was designed to provide insight into the real world of implementation of best practices in fall prevention in acute care Canadian hospitals. Approach Using case study methodology, ninety‐five administrative and point‐of‐care nurses at three hospitals participated in interviews or focus groups and provided documents and artifacts that described their implementation of a falls prevention guideline. Findings and implications Four recommendations with potential to guide others in fall prevention were identified: (1) the need to listen to and recognize the expertise and clinical realities of staff, (2) the importance of keeping the implementation process simple, (3) the need to recognize that what seems simple becomes complex when meeting individual patient needs, and (4) the need to view the process as one of continuous quality improvement.